Thermoelastic with photogenerated model of rotating microstretch semiconductor medium under the influence of initial stress - Abdulkafi M. Saeed (Elsevier, 2021)
A novel theoretical mathematical-physics model is obtained when the microstretch properties of elastic semiconductor medium are taken into account. This model is investigated in the context of photo-excitation transport processes through the thermoelasticity theory. The new model can be called Microstretch-photo-thermoelasticity (MPT) theory. The MPT model is studied under the impact of hydrostatic initial stress. The carrier’s charge field (carrier density or plasma wave) appears due to optical excitation. In this model, the interaction between thermal–mechanical-plasma waves is obtained when the medium is in a rotating case. When the medium is linear, isotropic and homogenous, the two-dimensional (2D) elastic and electronic deformations governing equations are investigated. This is done while taking into account the microinertia of the medium particles. The basic physical variables are obtained using the mathematical plane harmonic wave technique to obtain the general solutions. The complete analytical solutions are solved when conditions from mechanical-thermal and plasma type act at the free surface of the medium. The silicon (Si) and Germanium (Ge) materials are used to make the numerical simulations. The numerical results are displayed graphically and discussed.